First-year experience of a Brazilian tertiary medical center in supporting severely ill patients using extracorporeal membrane oxygenation - Marcelo Park; Luciano Cesar Pontes Azevedo; Pedro Vitale Mendes; Carlos Roberto Ribeiro Carvalho; Marcelo Brito Passos Amato; Guilherme Paula Pinto Schettino; Mauro Tucci; Alexandre Toledo Maciel; Leandro Utino Taniguchi; Edzangela Vasconcelos Santos Barbosa; Raquel Oliveira Nardi; Michelle de Nardi Ignácio; et al. (Clinics, 2012)
OBJECTIVES: The aim of this manuscript is to describe the first year of our experience using extracorporeal membrane oxygenation support. METHODS: Ten patients with severe refractory hypoxemia, two with associated severe cardiovascular failure, were supported using venous-venous extracorporeal membrane oxygenation (eight patients) or veno-arterial extracorporeal membrane oxygenation (two patients). RESULTS: The median age of the patients was 31 yr (range 14-71 yr). Their median simplified acute physiological score three (SAPS3) was 94 (range 84-118), and they had a median expected mortality of 95% (range 87-99%). Community-acquired pneumonia was the most common diagnosis (50%), followed by P. jiroveci pneumonia in two patients with AIDS (20%). Six patients were transferred from other ICUs during extracorporeal membrane oxygenation support, three of whom were transferred between ICUs within the hospital (30%), two by ambulance (20%) and one by helicopter (10%). Only one patient (10%) was anticoagulated with heparin throughout extracorporeal membrane oxygenation support. Eighty percent of patients required continuous venous-venous hemofiltration. Three patients (30%) developed persistent hypoxemia, which was corrected using higher positive end-expiratory pressure, higher inspired oxygen fractions, recruitment maneuvers, and nitric oxide. The median time on extracorporeal membrane oxygenation support was five (range 3-32) days. The median length of the hospital stay was 31 (range 3-97) days. Four patients (40%) survived to 60 days, and they were free from renal replacement therapy and oxygen support. CONCLUSIONS: The use of extracorporeal membrane oxygenation support in severely ill patients is possible in the presence of a structured team. Efforts must be made to recognize the necessity of extracorporeal respiratory support at an early stage and to prompt activation of the extracorporeal membrane oxygenation team.